THE REWARD OF WORSHIP IN RAMADHAN DURING COVID-19 PANDEMIC: A MATHEMATICAL ANALYSIS - Akhsanul Inam; Maya Rayungsari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2020)
This research aims at analyzing the rewards obtained from carrying out worship in Ramadhan during the Covid-19 Pandemic Period. The research approach applied was qualitative with the type of library research.  The objects of the research were prayer, reading Al Qur’an and Al-Hadith. The Covid-19 pandemic period, according to the regulation issued by the government of Indonesia in the form of social distancing, gave great impacts on the implementation of worship during Ramadhan. The data were analyzed based on the stipulations and guidelines of implementing the worship, especially during Ramadhan, which had been analyzed using mathematical calculations. The research results showed that the reward of implementing worship during the Covid-19 pandemic period was tremendous either in quantitative or qualitative calculations. In addition, it focused on the quality, so that the results of this research can be utilized as a basis for improving the quality of worship. AbstrakPenelitian ini bertujuan untuk menganalisis manfaat yang diperoleh dari melaksanakan ibadah di bulan Ramadhan selama Periode Pandemi Covid-19. Pendekatan penelitian yang digunakan adalah kualitatif dengan jenis penelitian kepustakaan. Objek penelitiannya adalah shalat, membaca Al-Qur'an dan Al-Hadits. Masa pandemi Covid-19, menurut aturan yang dikeluarkan pemerintah Indonesia berupa social distancing, berdampak besar pada penyelenggaraan ibadah selama Ramadhan. Data dianalisis berdasarkan ketentuan dan pedoman pelaksanaan ibadah khususnya pada bulan Ramadhan yang dianalisis menggunakan perhitungan matematis. Hasil penelitian menunjukkan bahwa pahala melaksanakan ibadah selama periode pandemi Covid-19 sangat besar baik secara kuantitatif maupun kualitatif. Selain itu juga menitikberatkan pada kualitas, sehingga hasil penelitian ini dapat dimanfaatkan sebagai dasar untuk peningkatan kualitas ibadah.